(untitled) (Fiep Bulletin - online, 2019)
The Body Culture is constituted by the set of knowledge socially produced and historically accumulated by humanityand manifested by the corporal expression. All African cultural influence was fundamental to the formation of the body of thecapoeirista. Capoeira, criminalized in the period of the Old Republic and later decriminalized under the government of GetúlioVargas, passed and goes through moments of devaluation and valorization in Brazilian society. Mestre Bimba and MestrePastinha were the great bastions that made this cultural manifestation, so traditional in Brazil, recognized and admired all overthe world. The research aims to study diverse aspects of the practices of Corporal Culture in Capoeira from the theme ofEducation, citizenship and exclusion. It will also analyze the historical and cultural dimensions of Capoeira in Brazil, especially inthe city of Rio de Janeiro, and how the process of black exclusion in Brazil occurred, in parallel with the sedimentation of theconcept of citizenship throughout the world.